Pandemic Guidance for Stroke Centers Aiding COVID-19 Treatment Teams. Issue 8 (August 2020) - Wira, Charles R.; Goyal, Mayank; Southerland, Andrew M.; Sheth, Kevin N.; McNair, Norma D.; Khosravani, Houman; Leonard, Anne; Panagos, Peter
Abstract : The coronavirus disease 2019 (COVID-19) pandemic has in some regions overwhelmed the capacity and staffing needs of healthcare systems, necessitating the provision of resources and staff from different disciplines to aid COVID treatment teams. Stroke centers have multidisciplinary clinical and procedural expertise to support COVID treatment teams. Staff safety and patient safety are essential, as are open lines of communication between stroke center leaders and hospital leadership in a pandemic where policies and procedures can change or evolve rapidly. Support needs to be allocated in a way that allows for the continued operation of a fully capable stroke center, with the ability to adjust if stroke center volume or staff attrition requires.